Pengembangan Mesin Belt Grinder Dengan Metode DFMA (Design For Manufacturing And Assembly) - Atmaja, Hikmah; Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
DFMA is defined as the design of a product or component which can facilitate the process of manufacturing and assembly process with other components to become a unified product. The grinding is a process that plays an important role in the production process or machining process. The belt grinder machine has a working principle by turning a belt-shaped sandpaper stacked on 4 rollers driven by an electric motor. This belt shaped round sandpaper is used to grind a surface such as drill, lathe tools and knives. Development of a simpler design is needed to increase the efficiency of time reduction in the assembly of belt grinder machines. Design development does not change the functionalities of each component of the product. The beginning of study, calculating the efficiency assembly of belt grinder product owned by Suheri's (2018). The next is development process of combination and elimination of components that do not affect the added value of the product. Suheri's belt grinder (2018) has 64 components with assembly efficiency of 7.29% and the results of engine design development have 43 components with assembly efficiency of 9.59%. Increase in assembly efficiency by 2.3% after development. Keywords: DFMA, grinding, belt grinder, assembly efficiency